Total hCG Versus Free β-hCG Combined with Alpha-fetoprotein for Down Syndrome Screening in Taiwan - Tsang-Tang Hsieh; Jenn-Jeih Hsu; Po-Jen Cheng; Chien-Nan Lee; Hei-Jen Jou; Chih-Ping Chen (Elsevier, 2007)
Objective: The purpose of this study was to compare the effectiveness between total human chorionic gonadotropin (hCG) and free β-hCG in two-marker Down syndrome screening programs during the second trimester in a Taiwanese population. Materials and Methods: From a multicenter collaborative study, we investigated the second-trimester maternal serum levels of total hCG from 67 data, free β-hCG from 72 and alpha-fetoprotein (AFP) from 96 obtained from Taiwanese pregnant women carrying fetuses with Down syndrome. Results: High total hCG and free β-hCG, as well as low AFP levels, were found with median values of 2.06, 2.49 and 0.77 multiples of the median (MoM), respectively. At a 5% false-positive rate, total hCG and free β-hCG could detect 31% and 43% of Down syndrome pregnancies, respectively, whilst AFP alone could detect only 15% of affected cases. When combined with maternal age-specific risk, total hCG could achieve a 52% detection rate, free β-hCG a 54% and AFP a 39%. Combined total hCG and AFP achieved a detection rate of 55%, and combined free β-hCG and AFP achieved a rate of 60%. Conclusion: The measurement of free β-hCG is more beneficial than total hCG in serum screening for Down syndrome during the second trimester of pregnancy.